IN VITRO ANTIPLASMODIAL ACTIVITY AND CYTOTOXICITY OF NEW N-BENZYL 1,10- PHENANTHROLINE DERIVATIVES - , Eti Nurwening Sholikhah, Mahardika Agus Wijayanti, Ruslin Hadanu ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
Our preliminary study showed that 1,10-phenanthroline skeleton was active in vitro on chloroquine-resistant and sensitive strains of Plasmodium falciparum. Based on the skeleton, 3 derivatives of N-benzyl 1,10-phenanthroline: (1)-N-(4-methoxy-benzyl)-1,10-phenanthrolinium bromide (1), (1)-N-(4-ethoxy-benzyl)-1,10-phenanthrolinium chloride (2), and (1)-N-(4-ethoxy-benzyl)-1,10-phenanthrolinium bromide (3) have been synthesized. This study was conducted to evaluate the in vitro antiplasmodial activity and cytotoxicity of these compounds. The antiplasmodial activity was tested in vitro against two strains of P. falciparum, FCR-3 and D10 while their cytotoxicity was tested against Vero cell line. The parasite growth was estimated by counting the percentage of infected erythrocytes within a thin blood film prepared after 24 and 72 hours incubation with each compound tested under a light microscope. The Vero cell growth was estimated by counting the percentage of viable cell after 24 and 72 hours incubation with each compound tested use MTT assay. The control parasite or cell free from any compounds was referred as 100% growth. The IC50 value showing concentration inhibiting 50% at the parasite or cell growth was determined by probit analysis. The results showed that all 3 compounds have antiplasmodial activity with IC50 value 0.82-3.04, 0.77-2.75, and 0.73-1.31 &mu